Understanding mobile application development and implementation for monitoring Posyandu data in Indonesia: a 3-year hybrid action study to build "a bridge" from the community to the national scale - Fedri Ruluwedrata Rinawan; Ari Indra Susanti; Indah Amelia; Mulya Nurmansyah Ardisasmita; Widarti; Rima Kusumah Dewi; Dani Ferdian; Wanda Gusdya Purnama; Ayi Purbasari (BMC, 2021)
Abstract Background Limited information is available on how mobile health (mHealth) application (app) technology on mother and child health (MCH) is developed. This research aimed (a) to explore the process of developing mobile apps for MCH community-based services in the Indonesian setting of Pos Pelayanan Terpadu (Posyandu/Integrated Health Service Post), (b) to determine the feasibility of using the app by community health workers (CHWs), and (c) to evaluate the scalability of the mobile app at the national level in Indonesia. Methods A hybrid method was used to synergistically combine the action research principles and mixed methods comprising qualitative and quantitative methods. This study was conducted in the Pasawahan District, Purwakarta, Indonesia, from 2017 to 2019. Content analysis, coding, and categorizing were performed using NVivo 12 Pro for transcribed data. The Wilcoxon test (2018 and 2019) was conducted using STATA 15 Special Edition. Results (1) The use of a CHW notebook for data entry into the Posyandu Information System book delayed the data reporting process, resulting in the need to develop a mobile app. (2) There were significant differences in CHWs' knowledge (p = 0.000) and skills (p = 0.0097) on training (2018) and Posyandu phases (2019). (3) A total of 964 Posyandu have been registered in the Posyandu mobile app from almost all provinces in Indonesia. Conclusions The three-year hybrid approach includes the crucial phases that are necessary to develop a mobile app that is more user-friendly and can act as a substitute for CHWs' book. Hence, its implementation is promising for use at the national level.